Các khái niệm và cách đo lường tài chính trong hoạt động khoa học và công nghệ - Hồ, Ngọc Luật (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article introduces several concepts of basic financial indicators in science and technology activities; analyzes the implications measurement units. It also introduces methodologies in measuring finance in science and technology activities to calculate accurately the total national investment and expenditure for science and technology. These concepts and methodologies are based on the guidance documents of UNESCO and OECD. The article also introduces methodologies to measure some financial indicators in science and technology, such as GERD, the gross domestic expenditure for research and development,... to standardize the concepts and methodologies in Vietnam as well as for international S&T statistical activities.